2005
DOI: 10.1007/s00424-005-1433-3
|View full text |Cite
|
Sign up to set email alerts
|

P2Y2 and P2Y4 receptors regulate pancreatic Ca2+-activated K+ channels differently

Abstract: Extracellular ATP is an important regulator of transepithelial transport in a number of tissues. In pancreatic ducts, we have shown that ATP modulates epithelial K+ channels via purinergic receptors, most likely the P2Y2 and P2Y4 receptors, but the identity of the involved K+ channels was not clear. In this study, we show by RT-PCR analysis that rat pancreatic ducts express Ca(2+)-activated K+ channels of intermediate conductance (IK) and big conductance (BK), but not small conductance (SK). Possible interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
44
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 47 publications
(62 reference statements)
3
44
0
Order By: Relevance
“…Low concentrations of UTP caused Ca 2+ oscillation and synchronous activity of K + currents, presumed to be IK channels, and pH i measurements indicated HCO À 3 secretion [131]. This finding supports conclusions drawn from studies on rat and human P2Y 2 receptors and IK channels [94,105]. In addition to P2Y 2 receptors, there are also P2Y 11 receptors on the basolateral membrane of canine epithelium that activate large Ca 2+ -independent Cl − conductance and cAMP increases (see Fig.…”
Section: Pancreatic Acinisupporting
confidence: 86%
See 4 more Smart Citations
“…Low concentrations of UTP caused Ca 2+ oscillation and synchronous activity of K + currents, presumed to be IK channels, and pH i measurements indicated HCO À 3 secretion [131]. This finding supports conclusions drawn from studies on rat and human P2Y 2 receptors and IK channels [94,105]. In addition to P2Y 2 receptors, there are also P2Y 11 receptors on the basolateral membrane of canine epithelium that activate large Ca 2+ -independent Cl − conductance and cAMP increases (see Fig.…”
Section: Pancreatic Acinisupporting
confidence: 86%
“…A similar effect of UTP on secretory processes was also detected in polarised Capan-1 cells, which are epithelial cells derived from pancreatic adenocarcinoma [104]. RT-PCR analysis of the single rat ducts revealed that they express Ca 2+ -activated K + channels of the intermediate conductance (IK also known as SLO, Maxi K and KCNMA1) and big conductance (BK also known as SK4, KCNN4) [105]. Human IK or BK channels were coexpressed with hP2Y 2 or hP2Y 4 receptors in Xenopus oocytes and cell currents were measured.…”
Section: Pancreatic Acinimentioning
confidence: 62%
See 3 more Smart Citations